Influence of Temperature and Relative Humidity on Spore Germination and Early Blight Disease Development of Tomato Caused by Alternaria solani - Attri, Kaushal; Gupta, Pankaj; Kansal, Sandeep; Gupta, Meenu; Goswami, Manika; Thakur, Shavnam (International Journal of Economic Plants, 2024)
Early blight of tomato caused by Alternaria solani is one of the most important and devastating disease of tomato which causing extensive yield losses to the crop. Environmental factors play an important role in the development of disease. To investigate the congenial conditions to develop the disease and germination of fungal spores an experiment was conducted in the year 2019 and 2020 at vegetable pathology laboratory of Dr Yashwant Singh Parmar University of Horticulture and Forestry Nauni Solan, Himachal Pradesh, India. Under investigations effect of temperature and relative humidity (RH) on conidial germination and early blight diseases development of tomato caused by Alternaria solani was studied under in vitro and in vivo conditions. Under in vitro conditions, maximum germination of conidia (75.54%) was recorded at 30°C after 24 hours and minimum (23.24%) was recorded at 15°C. length of germ tube (129.55 µm) was maximum at 25°C, whereas, minimum (67.09 µm) was observed at 15°C. In case of relative humidity maximum conidial germination (95.18%) and germ tube length of 238.95 µm was observed at 100% level. Under in vivo conditions disease severity was maximum (81.48%) at 30°C followed by 25°C (78.21%), whereas, minimum (18.88%) was recorded at 40°C. Similarly, the maximum (88.09%) disease severity was observed at 100% RH level while, it was minimum at 38% level of humidity. Overall, the relative humidity of more than 90% and temperature range of 25–30°C was found most congenial for the development of disease.